A General Framework for Comparing Predictions and Marginal Effects across Models. Issue 1 (August 2019) - Mize, Trenton D.; Doan, Long; Long, J. Scott
Many research questions involve comparing predictions or effects across multiple models. For example, it may be of interest whether an independent variable's effect changes after adding variables to a model. Or, it could be important to compare a variable's effect on different outcomes or across different types of models. When doing this, marginal effects are a useful method for quantifying effects because they are in the natural metric of the dependent variable and they avoid identification problems when comparing regression coefficients across logit and probit models. Despite advances that make it possible to compute marginal effects for almost any model, there is no general method for comparing these effects across models. In this article, the authors provide a general framework for comparing predictions and marginal effects across models using seemingly unrelated estimation to combine estimates from multiple models, which allows tests of the equality of predictions and effects across models. The authors illustrate their method to compare nested models, to compare effects on different dependent or independent variables, to compare results from different samples or groups within one sample, and to assess results from different types of models.